HUBUNGAN STATUS GIZI DENGAN KEMAMPUAN MOTORIK KASAR SISWA KELAS IIB DI SEKOLAH DASAR NEGERI 037 PEKANBARU - Nafaliana, Nafaliana; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Adsolescence is a very decisive time, because at this age the childrenexperienced many changes to the psychic and physical. Growth and development willrun optimally when children get stimulation in the form of physical stimulation andhealthy and nutritious food, because one of the supporting factors for motor skills isnutritional status. This study attempts to determine the relationship between nutritionalstatus and gross motor ability of class IIb students at State Elementary School 037Pekanbaru. The method of this research was used quantitative with correlation studies.The quantitaty of respondents in this research were 30 samples. Data were obtained bymeasuring anthropometric tests of weight and height for nutritional status variables,and gross motor ability tests which included: agility test with a shuttle run, a tennis ballthrowing coordination test, a balance test with a Stork stand positional balance, and aspeed test with running. fast 30m. The analysis used is Product Moment Correlationanalysis. From the calculation, the research results obtained a correlation value of0.981, which means it is associated with a very strong level, so that r count > r table,which means that there is a significant relationship between nutritional status and grossmotor ability of grade IIb students at State Elementary School 037 Pekanbaru.Key Words: Nutritional Status, Gross Motor Ability